2021
DOI: 10.1164/rccm.202101-0122oc
|View full text |Cite
|
Sign up to set email alerts
|

Addition of 5% CO2 to Inspiratory Gas Prevents Lung Injury in an Experimental Model of Pulmonary Artery Ligation

Abstract: This author conceived, planned and carried out the experiments, interpreted the results, and wrote the manuscript. A.M, L.M., Y.W.: These authors carried out the experiments and collected the results. G.C.: This author processed experimental data. O.B., M.B.: These authors helped in the implementation of the experiments. F.R.: This author collected and processed biological samples and analyzed the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“… Peltekova et al (2010) also demonstrated a similar decrease in MCP-1 and IL-6 in a mouse model of lung injury treated with hypercapnia ( Peltekova et al, 2010 ). A recent investigation in previously healthy pigs with unilateral ligation of the pulmonary artery ( Marongiu et al, 2021 ) found that inhaled CO 2 5% prevented an inflammatory reaction otherwise developing in both lungs. Of note, the driving pressures were significantly reduced in the iCO 2 5% group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Peltekova et al (2010) also demonstrated a similar decrease in MCP-1 and IL-6 in a mouse model of lung injury treated with hypercapnia ( Peltekova et al, 2010 ). A recent investigation in previously healthy pigs with unilateral ligation of the pulmonary artery ( Marongiu et al, 2021 ) found that inhaled CO 2 5% prevented an inflammatory reaction otherwise developing in both lungs. Of note, the driving pressures were significantly reduced in the iCO 2 5% group.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the driving pressures were significantly reduced in the iCO 2 5% group. The alveolar and arterial CO 2 was double in the intervention group and ventilation-perfusion relationships (Va/Q) were not measured; it remains unclear whether the observed effects were predominately caused by the exogenous CO 2 or by a more favorable Va/Q allowing protective ventilation settings (hen-or-egg theorem) ( Marongiu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study conducted by our group showed that the addition of 5% CO 2 to inspiratory gas prevents bilateral VILI in an experimental model of ligation of the left pulmonary artery ( 12 ). Mechanisms of protection included decreased inflammation in both lungs and more homogeneous distribution of ventilation, with reduced overdistension of the right lung.…”
Section: Introductionmentioning
confidence: 99%
“…From the Authors, We thank Dr. Ajay Kumar Jha for the insightful comments on our recent experimental study [1]. Indeed, the experiment offers food for thoughts as we are at the very beginning of understanding pathophysiological changes induced by unilateral pulmonary artery ligation (UPAL) and mechanisms of lung protection by inhaled 5% CO 2 .…”
mentioning
confidence: 99%